Prevalence and management of delirium in intensive care units in the Netherlands: An observational multicentre study. (December 2020) - Berger, Elke; Wils, Evert-Jan; Vos, Piet; van Santen, Susanne; Koets, Jeroen; Slooter, Arjen J.C.; van der Woude, Meta; Koopmans, Matty; Rinket, Martin A.; Hoiting, Oscar; Hoogendoorn, Emma E.; Streefkerk, Jörn O.; et al.
Abstract: Objectives: This study aimed to determine the prevalence, risk factors of delirium and current practice of delirium management in intensive care units of various levels of care. Research methodology/design: Prospective multicentre cohort study. Setting: In all adult patients admitted to one of the participating intensive care units on World Delirium Awareness Day 2018, delirium point and period prevalence rates were measured between ICU admission and seven days after the index day. Results: In total, 28 (33%) Dutch intensive care units participated in this study. Point-prevalence was 23% (range 41), and period-prevalence was 42% (range 70). University intensive care units had a significantly higher delirium point-prevalence compared with non-university units (26% vs.15%, p = 0.02). No significant difference were found in period prevalence (50% vs. 39%, p = 0.09). Precipitating risk factors, infection and mechanical ventilation differed significantly between delirium and non-delirium patients. No differences were observed for predisposing risk factors. A delirium protocol was present in 89% of the ICUs. Mean delirium assessment compliance measured was 84% (±19) in 14 units and estimated 59% (±29) in the other 14. Conclusion: Delirium prevalence in Dutch intensive care units is substantial and occurs with a large variation, with the highest prevalence in university units. Precipitating risk factors were more frequent in patients with delirium. In the majority of units a delirium management protocol is in place.